2007
DOI: 10.1097/fjc.0b013e31803c5616
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidin Extracts Inhibit Vascular Cell Adhesion Molecule Expression Induced by Advanced Glycation End Products Through Activation of Peroxisome Proliferators-Activated Receptor γ

Abstract: Although evidence has shown that grape seed proanthocyanidin extracts (GSPE) can selectively inhibit cell adhesion molecule expression induced by advanced glycation end products (AGEs), the underlying molecular mechanism has not been extensively characterized. To study the antiinflammation mechanism of GSPE, we investigated the effect of GSPE on Von Willebrand factor (vWF) content and the expression of vascular cell adhesion molecule-1 (VCAM-1) induced by AGEs and the effect of GSPE on peroxisome proliferators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…It has been reported that GSPEs have antioxidant properties, as evidenced by the increase in pancreatic glutathione and reduction of lipid peroxidation, so it might have improved the function of cells in the diabetic rat, and influenced insulin effects by acting directly on specific components of the insulinsignaling transduction pathway. 19,37) GSPEs reduced aortic wall stiffness in the diabetic rats, with no change in wall stress. This observation is in line with the hypothesis that AGE-induced cross-linking of scleroproteins in adult animals increases the aortic EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that GSPEs have antioxidant properties, as evidenced by the increase in pancreatic glutathione and reduction of lipid peroxidation, so it might have improved the function of cells in the diabetic rat, and influenced insulin effects by acting directly on specific components of the insulinsignaling transduction pathway. 19,37) GSPEs reduced aortic wall stiffness in the diabetic rats, with no change in wall stress. This observation is in line with the hypothesis that AGE-induced cross-linking of scleroproteins in adult animals increases the aortic EM.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Our previous experiments showed that GSPEs displayed anti-nonenzymatic glycation and anti-inflammation, reducing receptor of advanced glycation end product (RAGE) protein expression, leading to decreased expression of high level vascular cell adhesion molecule 1 induced by advanced glycation end products (AGEs) in endothelial cells. 18,19) In our present study, we examined the effects of AGEs on the diabetic aorta and evaluated the efficacy of aortic protection by GSPEs. Moreover, aortic function was assessed by measurement of aortic PWV, EM, and * Xiao-li Li and Bao-ying Li contributed equally to this work.…”
Section: )mentioning
confidence: 99%
“…The transmembrane receptor receptor for advanced glycation endproducts was shown to be the receptor for S100 proteins (54)(55)(56), potentially including S100A4 (55)(56)(57). Receptor for advanced glycation endproducts protein is expressed in HUVEC cells (58,59), implicating secreted S100A4 as a new paracrine executioner of RLN2 actions in thyroid carcinoma angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that procyanidins inhibited platelet aggregation [40] and had also successfully inhibited the oxidation of low-density lipoprotein (LDL) as well as contributed to reduction in risks of heart disease associated with atherosclerosis [41]. In addition, procyanidins performed very well as anti-inlammatory [42,43], antimutagens [44], anticancer [45][46][47], and antiviral [48] agents.…”
Section: Biological Activitiesmentioning
confidence: 99%